2016
DOI: 10.1111/ffe.12489
|View full text |Cite
|
Sign up to set email alerts
|

Macromechanics study of stable fatigue crack growth in Al–Cu–Li–Mg–Ag alloy

Abstract: This study was made on a fresh variety of Al–Li base alloy to investigate the role of ageing precipitates and microstructure dimensions in the fatigue crack growth resistance. The fatigue crack growth rate was measured in three different states of the material (i.e. base metal in T8 condition, friction stir weld and laser beam weld in full‐aged condition). Metallurgical analysis showed that the base metal in T8 temper is precipitation hardened by an equivalent amount of δ′ (AL3Li), T1 (AI2CuLi) and θ′ (AI2Cu) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…It can be observed that the tensile strength is comparable to similar material [18,31] but higher than several other types of Al-Li alloys [3,7,19,24,34] reported in the literature. It has been shown that increase in the Cu and Li contents of the alloy promotes the formation of strengthening precipitates such as Al2CuLi and Al2Cu phases which increase the alloy's strength [13,24,35]. Aging condition, homogenization heat treatment, orientation of testing and precipitate phases have been identified as vital factors which influence the alloy's tensile properties [5,18,21,22,31].…”
Section: Static Tensile Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…It can be observed that the tensile strength is comparable to similar material [18,31] but higher than several other types of Al-Li alloys [3,7,19,24,34] reported in the literature. It has been shown that increase in the Cu and Li contents of the alloy promotes the formation of strengthening precipitates such as Al2CuLi and Al2Cu phases which increase the alloy's strength [13,24,35]. Aging condition, homogenization heat treatment, orientation of testing and precipitate phases have been identified as vital factors which influence the alloy's tensile properties [5,18,21,22,31].…”
Section: Static Tensile Behaviormentioning
confidence: 99%
“…However, challenges such as prohibitive cost, poor fatigue performance, low fracture toughness, poor corrosion resistance and high anisotropic behavior constrained the wide deployment of Al-Li in the aircraft industry [1,2,7,8]. Perhaps, poor fatigue performance is the larger reason that sundry works on different generations of the alloys were focused on fatigue crack behavior [9][10][11][12][13][14][15]. While there is growing research interest in the tensile behavior of the Al-Li, fatigue studies of the alloy are scarce in the open literature.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Antunes investigated the main numerical parameters affecting PICC. The importance of RICC on fatigue crack propagation has also been investigated; for example, Akhtar proposed that the superior fatigue crack growth resistance of the weldment could be attributed to the occurrence of RICC mechanism. Silva made roughness measurement experiments and concluded that at negative stress ratios, RICC was not a relevant mechanism.…”
Section: Theoretical Considerationsmentioning
confidence: 99%
“…In their studies, these researchers have used a range of methods from a simple tensile loaded plate to more complex structural components under both uniaxial and mixed‐mode loading conditions. Huffman, Shi et al, Kujawski and Ellyin, Li et al, Noroozi et al, Song et al, Tong et al, and Akhtar et al are some of the researchers who have studied the fatigue behaviour of cracked components under uniaxial or multiaxial non‐linear loading conditions. In some cases, the effect of the mean stress on the fatigue crack behaviour was also assessed.…”
Section: Introductionmentioning
confidence: 99%